The Portrayal of the Main Character’s Hegemonic Masculinity Dispositions in Natsume Soseki’s Botchan: A Gender Study Perspective - Nicholas Krishnamurti Wibowo; Maria Vincentia Eka Mulatsih (FKIP, Universitas Palangka Raya, 2024)
Literature can be the window to discern new perspectives about life and broaden the reader’s horizons. Botchan by Natsume Soseki is a novel that has a big theme about morality which can be comprehended by the archetypes of the people from a big city and remote area, yet the polemic that appeared is rooted in the discrepancy of the characters’ dispositions. The writers attempt to analyze it in the frame of gender study which later gets elaborated with the hegemonic masculinity in two questions: “In what way does Botchan represent hegemonic masculinity?” and “How do the hegemonic masculinity dispositions within Botchan affect Botchan’s relations with Hotta, Mr. Yoshikawa, and Red Shirt?” The writers utilized the close reading method alongside the gender study approach. The hegemonic masculinity from Botchan attracts the character with a similar disposition (Hotta) and dissociates with Red Shirt and Mr. Yoshikawa that do not embody hegemonic masculinity dispositions. The indicator for hegemonic masculinity is determined by multiple factors, such as strength, competitiveness, assertiveness, confidence, and independence. Hegemonic masculinity is a glimpse of the extensive range of the definition of masculinity, therefore it is fenceless for arguments from other notions.